Effectiveness of Oral Magnesium in Chronic and Episodic Migraine: An Evidence-Based Case Review - Ayu Andin Wardani, Mutia; Sunardi, Diana (Fakultas Kedokteran, Universitas Andalas, 2026)
Background: Chronic migraine (≥15 headache days per month) and episodic migraine (<15 headache days per month) are disabling neurological disorders affecting more than one billion people worldwide. Conventional prophylactic therapies, including beta blockers and antiepileptics, may be effective but are often associated with tolerability concerns. Magnesium, an essential mineral involved in vascular regulation and neuronal function, has been proposed as a safe and low-cost alternative for migraine prevention. Objective: To evaluate the effectiveness of oral magnesium supplementation in reducing migraine frequency and intensity through an evidence-based case review. Methods: A systematic literature search was conducted in PubMed, Scopus, Cochrane Central, and Google Scholar. Randomized controlled trials and systematic reviews comparing oral magnesium with placebo or standard prophylactic therapy were included. Results: Seven studies (three randomized controlled trials and four systematic reviews) were identified. Overall, oral magnesium reduced migraine frequency and pain severity, although substantial heterogeneity in formulation, dosage, and study design was observed. Conclusion: Oral magnesium appears safe, inexpensive, and well tolerated, but further high-quality trials are needed to determine optimal dosing and comparative efficacy.